Effects of polypropylene fibres and steel fibres on fire resistance of ultra high performance concrete - Chua, Yingxuan (2016)
Concrete has been a great discovery for the advancement of building material technology for the past few decades. In recent times, the creation of High Performance Concrete (HPC) has added more abilities of a concrete into its usage. However, the risk of explosive spalling is still a concern for HPC under the exposure of fire. Explosive spalling not only weaken its ability to carry load, the loss of cover exposes the steel reinforcement within the concrete, allowing it to be further weakened by the fire. Particularly so when the structure or building is underground, the extent of damage by fire is much greater than when it is not. Research has been done to prevent spalling, but a proven method is still not available currently. This report hopes to provide some insight into the research of explosive spalling prevention. By identifying the factors that influence explosive spalling, the methods to test the factors and the discussion of the results of the tests, this report investigates the causes of spalling in detail. The three main assumptions of spalling are namely, pore pressure induced stress, thermal gradient induced stress and combination of pore pressure and thermal stress. One main factor that has been identified which has decisive influence on spalling is permeability. Four different factors are made to HPC to investigate the fire effect on the mechanical properties of concrete such as compressive strength and uniaxial tensile strength. The four factors are amount of silica fume, aggregate size, steel fibre content and PP fibre content. Using a mix design with maximum strength, the specimens went through elevated temperature for the testing of permeability. The result of permeability is discussed with the results of the spalling test of each specimen.